Surgical approach in symptomatic myocardial bridge - Rahman, A.; Burma, O.; Uyar, I.S.; Karaca, I.; Ilkay, E.; Cekirdekci, A. (Asia Publishing Exchange Pte Ltd, 2000)
Between 1996 and 1998, surgery was carried out in 4 patients with myocardial bridging who had angina refractory to medical therapy. Two patients were treated by supraarterial myotomy and 2 underwent coronary artery bypass grafting. One patient suffered a right ventricular perforation that was successfully repaired. Surgery is recommended for a grade-III myocardial bridge.
Keywords: acetylsalicylic acid; dipeptidyl carboxypeptidase inhibitor; glyceryl trinitrate; adult; aged; angina pectoris; angiocardiography; article; case report; coronary artery bypass graft; human; male; myocardial disease; myotomy; perforation